Estimating biological reference intervals for cell blood counts in a dog population (2021)
ABSTRACT : Background: The results from automated equipment and peripheral blood smears allow correlating clinical data with cellular blood counts (CBC), generating information on pathologies of hematological and non-hematological origin in dogs. Objective: To describe qualitative and quantitative magnitudes of CBC in healthy donor dogs of a blood- bank in Medellín (Colombia). Methods: A descriptive-prospective study was carried out from 146 records of CBC results from a blood-bank. The samples were processed by automated equipment, and trained personnel performed the observation of peripheral blood smears to collect qualitative information. Variables such as age, sex, breed, quantitative results, and observations of the peripheral blood smears were considered. For the definition of biological intervals (BIs), the mean and two standard deviations were used for the data with a normal distribution. Otherwise, the 2.5th and 97.5th percentiles were used. Results: The size, granularity, and cytoplasmic vacuoles in monocytes and polymorphonuclear eosinophils, as well as the presence of Barr chromatin and occasional circulating erythroblasts, were remarkable findings to the peripheral blood smear. With the standardization of data obtained from dogs of large and giant breeds, the present work provides BIs for some of the CBC data in the studied population. Conclusion: The findings of the present study allow approximations to the definition of alterations in blood cells and their counts, which can guide the veterinarian towards an early diagnosis in dogs.